Exploring the Coroner System within the United States (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
In the present day, the United States does not have a standardized system in place  for medicolegal death investigations. Within the 50 U.S. states and 16 territories,  there is variability regarding whether the coroner or medical examiner system is  utilized. These systems can then be broken down further into; centralized state  medical examiner’s offices, county or district medical examiner’s offices, mixed system states (both coroners and medical examiners are utilized), and coroner-only  states. Certain states may have coroners that are also under the title of “justice of the  peace” (Texas) or “sheriff-coroner” (California). Below is a list of which states and  territories fall into their respective systems:
Keywords: sheriff-coroner; board-certified; medicolegal; pathologists